Exploring tourism experiences: comparative trends and hotspots in Chinese and American research - Zhang Yaling; Asad Ur Rehman; Ihtisham Ullah; Ayesha Nawal; Kashif Hussain (Cogent Business & Management)
This paper explores tourism experiences through a comparative analysis of research trends and hotspots in China and the United States. Using CiteSpace software, it analyzes relevant literature from 1 January 2004 to 10 May 2024. The research reveals that although China started later in tourism experience research, it has developed rapidly and formed unique features. Both countries attach importance to tourism experiences and the application of technology. However, in the initial stage, China focused on infrastructure construction and tourism industry development planning, while the US emphasized concept definition, theoretical framework construction, and in—depth evaluation of tourism experience quality. This study fills the gap in cross—cultural comparison of tourism experience research, provides a scientific basis for the comparative analysis of Chinese and American tourism experience research, and promotes the theoretical development and practical innovation in this field.